Genetic Variation Studies in Natural Populations of Neoza Pine (Pinus gerardiana) - Sharma, Rajesh (Indian Forester, 2017)
The genetic variation of Neoza pine (Pinus gerardiana) populations with restricted distribution confined to arid regions of the temperate Himalayas was studied. These populations located in Kinnaur and Chamba districts of Himachal Pradesh showed difference with regard to both quantitative and qualitative traits. The performance of selected individuals (Plus Trees) within populations showed significant differences for nursery traits. The evaluation of twelve populations of Noeza pine through isozymes using six enzyme systems recorded 14 gene loci of which 6 were polymorphic with 2-3 alleles per locus. Of the 16 alleles found encoded for 6 polymorphic gene loci, SKDH-A3 was rare for its observance in only two populations with one per cent frequency. The differences were observed among populations allelic and genotypic differentiation between and within gene loci among populations, heterozygosity and genetic distance. The mean heterozygosity value varied from 0.17 to 0.21 for population 9 to 1, 5, 6 and 11. Genetic distance values ranged from 0.009 between populations 6 and 10 to 0.039 between populations 3 and 12. The pattern of grouping for nearly the same values of diversity and differentiation among the populations despite altitudinal differences suggest common descent of the populations. The populations with greater genetic diversity values need to be conserved and made use of in future tree improvement programmes of the species.